Strategi Komunikasi Politik Digital Calon Legislatif di Media Sosial: Studi Kasus Platform Twitter Dan Facebook - Ardha, Berliani (Jurnal Riset Komunikasi, 2025)
This study aims to analyze the digital political communication strategies employed by legislative candidates through social media in their efforts to build electability during the 2019 general election. A case study was conducted on a legislative candidate from the Democratic Party running for the Jakarta Regional House of Representatives (DPRD DKI Jakarta), who actively used Twitter and Facebook to convey political messages, present policy proposals, and engage with voters. The research employed a qualitative method with a case study approach, utilizing in-depth interviews, observations, and documentation. The findings indicate that social media plays a significant role in enhancing political visibility and interaction with constituents, although it does not directly translate into an increase in electoral votes. The candidate's focus on education and healthcare issues was found to be effective in garnering support from the digital public, especially on Facebook. Meanwhile, Twitter was utilized to construct a more dynamic and responsive political image